Understanding Associations Between Low-Income Mothers' Participation in Education and Parenting. Issue 4 (2nd October 2017) - Harding, Jessica F.; Morris, Pamela A.; Hill, Jennifer
ABSTRACT: Maternal education is one of the strongest predictors of children's academic outcomes. One possible explanation for this is that more highly educated mothers more frequently engage in parenting practices that may promote children's later cognitive development; however, most of this evidence is correlational. This study uses Head Start Impact Study data ( N = 1, 953) to explore whether low-income mothers' participation in education affects their parenting practices and beliefs. Principal scores, which predict maternal educational participation based on covariates, were used for analysis. Principal score matching was used to identify mothers who we predicted participated in education because their children were randomly assigned to Head Start. We compared these mothers' outcomes to those of mothers we predicted would have participated in education if they were assigned to Head Start. For these mothers, participation in maternal education was associated with children watching fewer hours of TV, having more types of printed media at home, and more frequent participation in cultural activities, but it was not associated with a host of other parenting outcomes. Changing parenting is one potential pathway by which maternal educational participation may influence children's later academic outcomes.